"It's not what you see but what you hear…": Understanding environment protection officers' responsive decision making. (15th May 2020) - Curtis, Jim; Kaufman, Stefan
Abstract: Responsive regulation asserts that regulatory enforcement actions are likely to be more effective in promoting compliance when they respond to a duty holder's motives, capabilities, and external pressures. However, operationalizing responsive approaches that also possess qualities of consistency and transparency remains a challenge for environmental management authorities. This study applied a mixed-method qualitative approach to capture the responsive decision making influences on government environment protection officers in a field context when engaging with different duty holders. These insights then informed compliance narratives across a series of business behavior segments to guide more consistent, transparent and responsive decision making among environment protection officers. Our findings revealed how different constellations of observations, interactions and displays of willingness and ability impact the choice of regulatory responses. Challenges encountered in applying responsive regulation in practice involved difficulties ascertaining business capability, identifying causal links between response strategies and compliance outcomes, and how the use of discretion can impact on consistent and transparent decision making. Highlights: Responsive regulation can be a challenge for environmental management authorities. Regulatory responses need to be guided by an understanding of duty holders. The experiences of environment protection officers are an underutilised resource. Compliance narratives are developed for different duty holder types. Guide more consistent, transparent and responsive decision-making.